The role of graphite foam pore structure on saturated pool boiling enhancement - Pranoto, I. (2013)
This paper presents an experimental study of the pool boiling phenomena and performance of porous graphite foam evaporators of different structures and thermophysical properties. Two dielectric liquids viz. FC-72 and HFE-7000 were used as working fluids. Block and fin evaporators of different fin-to-block-surface-area ratios (AR) were designed to study the role of the internal pore structure of graphite foams in a compact air-cooled thermosyphon under saturated pool boiling condition for high heat flux electronics cooling applications. The wall temperatures were measured and the boiling heat transfer coefficients were calculated to analyze the boiling performance. It was found that both fin structures with AR = 3.70 and 2.73 result in reduced boiling heat transfer performances and higher wall temperatures. The experimental results show that the boiling heat transfer coefficients of the block structures are about 1.2–1.6 times higher than those of the fin structures. The total internal surface area to volume ratio (β) and the total exposed areas (AT) of the graphite foams were calculated in this study. The results show that the values of β and AT of the block structures are much higher than the fin structures for both tested “Pocofoam” 61% porosity and “Kfoam” 78% porosity evaporators which resulted in higher boiling heat transfer coefficient and lower wall temperature of the block structures. A visualization study shows that more bubbles were generated from the block structures compared to the fin structures due to the larger number of nucleation sites from the block structures. It was also found that use of FC-72 resulted in better boiling heat transfer performance compared to HFE-7000.